Relação entre o tamanho do fruto e o número de septos e número de sementes em tangerina-satsuma (Citrus unshiu Marc) ev. 'owari' - Nagrib Jorge Chalfun, Nilton; Lopes Teixeira, Sílvio (Revista Ceres, 2025)
This work, carried out at Viçosa, Minas Gerais, was a study of correlation between fruit size and number of seeds and number of septa in the Satsuma tangerine (Citrus unsiu Marc, cv. «Owari»).